Project-based Activities and Startup Movement in Creative Industries as a Field of Mentorship in Higher Education - G. I. Gumerova; E. Sh. Shaimieva (Управленческие науки)
This article presents the findings of a study on the development of project-based activities in the creative industries, examined as a field of mentorship in higher education. The authors emphasize that the creative industries, with their intellectual and often collaborative or project-based nature, act as a driver of the modern economy. The research employed scientific methods such as analysis, synthesis, and classification. The informational base consisted of data from the Scientific Electronic Library (NEB), materials from Google Scholar relevant to the topic, and methodological resources on mentorship within the Russian economic framework (both federal and regional levels). The aim of the study was to explore the essence of mentorship in higher education within the context of project-based activities in the creative industries and to develop tools for effective project mentoring in this domain. The outcomes of the research include a refined definition of “projectbased mentorship in higher education,” a rationale for the need to study a Russian mentorship model, identification of ten specific forms of mentorship, the creation of a conceptual framework for project mentoring in the creative industries in higher education, and the development of original initiatives to support its advancement. These results may be used to promote the Russian model of mentorship on the global stage. The findings may also be useful to university project participants, startup mentors, and creative industry professionals.